Comparison of shear bond strength of stainless-steel orthodontic brackets bonded with different adhesives and bonding agents - Faezeh Zamani; Mohammad Ali Moghaddam; Mostafa Sheikhi (Mashhad University of Medical Sciences, 2023)
Introduction: The type of bonding agent and adhesive can play an important role in the bond strength of orthodontic brackets. This study measured and compared the shear bond strength (SBS) of brackets bonded with Z250 and Denu adhesives, as well as two different types of bonding agents (Single Bond and Denu Bond).Methods: In this in vitro study, 80 intact premolars were randomly divided into four groups (20 teeth per group). The brackets were bonded to the teeth in the following order: group A: Single Bond + Z250 adhesive; group B: Denu Bond + Z250 adhesive; group C: Single Bond + Denu adhesive; and group D: Denu Bond + Denu adhesive. The SBS values were recorded using a universal testing machine, and Adhesive Remnant Index (ARI) scores were determined. The data were analyzed by ANOVA and Fisher's exact test at a significance level of 0.05.Results: The mean SBS values of the A, B, C, and D groups were reported as 16.66, 17.21, 14.61, and 15.91 MPa, respectively. No significant difference was found among the groups in terms of SBS and ARI scores (P=0.06 and P=0.78, respectively).Conclusion: The Denu adhesive can be used as a clinical alternative to commercial adhesives, such as Z250, for bonding metal orthodontic brackets. Moreover, bonding agents and adhesives from different companies can be used simultaneously.  (J Dent Mater Tech 2023;12(1): 10-15)